1999
DOI: 10.4269/ajtmh.1999.61.288
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis vaccine (inactivated, BIKEN) in U.S. soldiers: immunogenicity and safety of vaccine administered in two dosing regimens.

Abstract: Abstract. The safety and immunogenicity of Japanese encephalitis (JE) vaccine (Nakayama strain, monovalent / BIKEN) was studied in 538 U.S. soldiers in 1990. Three doses of vaccine from three consecutively manufactured lots were given on days 0, 7, and either 14 or 30. Serum for antibody determination was drawn at months 0, 2, and 6. Japanese encephalitis plaque reduction neutralization tests were performed by three laboratories on each specimen. Five hundred twenty-eight (98%) participants completed the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…Higher rates of AEs were found in Denmark; the rate of allergic mucocutaneous reactions was 73/350,000 doses and rate of any AEs was 101/350,000 doses) [40]. Other studies have found that while local, mild reactions are common, low rates of serious adverse events occur, though few have had sufficient sample sizes and follow up times to detect rare neurological events [31,38,41,42,46,[48][49][50][51][52][53]. Overall rates of local reactions has been estimated around 20%, mild systemic at 10-30%, hypersensitivity at 1-64/10 000 and acute encephalitis at 1/75 000 to 1/ million doses [1].…”
Section: Adverse Events and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Higher rates of AEs were found in Denmark; the rate of allergic mucocutaneous reactions was 73/350,000 doses and rate of any AEs was 101/350,000 doses) [40]. Other studies have found that while local, mild reactions are common, low rates of serious adverse events occur, though few have had sufficient sample sizes and follow up times to detect rare neurological events [31,38,41,42,46,[48][49][50][51][52][53]. Overall rates of local reactions has been estimated around 20%, mild systemic at 10-30%, hypersensitivity at 1-64/10 000 and acute encephalitis at 1/75 000 to 1/ million doses [1].…”
Section: Adverse Events and Toxicitymentioning
confidence: 99%
“…For travellers from non-endemic countries the three dose regimen is shortened to days 0,7 and either 14 or 30 [29]. A study in the US showed that both these regimens have good immune responses, with higher titres for the 30 days regimen [38]. Hence travellers with shorter deadlines can still benefit from the 2 week regimen.…”
Section: Generalised=5%mentioning
confidence: 99%
“…There were approximately 22,000 Thai schoolchildren in each of these recipient groups. The efficacy of both monovalent and bivalent vaccines was 91%, achieved with minor vaccine adverse effects (headache, sore arm, rash, and swelling), and these data [88][89][90][91] were pivotal in obtaining FDA licensure of JE-VAX -a formalin-inactivated whole virus vaccineon 10 December 1992. This large clinical trial was facilitated by (1) development of a new IgM test by Donald Burke at AFRIMS and (2) the comprehensive placebo-controlled study of the BIKEN vaccine in volunteers in the 25th Infantry Division in Hawaii, which demonstrated that the vaccine was safe and antibody levels persisted 3 years after immunization [88,92,93].…”
Section: Japanese Encephalitis Vaccine and Current Related Researchmentioning
confidence: 99%
“…(7,(165)(166)(167)(168) The FDA licensed JE vaccine in 1992. Because of an uncommon risk of delayed-onset urticaria and angioedema, the vaccine's labeling recommends deferring travel for 7 to 10 days after immunization.…”
Section: Immunization To Protect the Us Armed Forces 14mentioning
confidence: 99%